Não queremos que se sinta assim! Vamos te ajudar!: práticas discursivas nas interações entre empresas e consumidores no facebook - MOURA, Murilo Coelho de (Universidade Federal do Pará, 2019)
Since yours emergency, in the mid 1990’s, the social media has made many changings in the social interactions. But it wasn’t only the social interactions affected by the popularization of social media, the work interactions have also affected by the changes in the new participation society. In this way, this research addresses the discursive practices that enterprises and consumers act in Facebook and the mode of enunciation accordingly with such practices, in order to recognize how enterprises and consumers establish and articulate the modes of enunciation of those practices in theirs interactions in Facebook. Supported by French Discourse Analysis, especially in the studies of Maingueneau (1997, 2008a, 2008b, 2011, 2015) about the notions of enuciative scene, discursive practice and midium, we understand that is relevant investigate such processes articulating the linguistic dimension and the social historic dimension that implies ways of saying and of doing, that also implies social relations reorganization and the use of power to say and to stop talking. The analysis that we develop is divided in three parts, according with the material analyzed: the enterprises’ posts, the consumers’ comments, and the enunciators of enterprises and consumers’ replies. From this triple analysis, we concluded that the interaction between enterprises and consumers in Facebook is conducted by a tension between discursive practices: in one side, the organizational discursive practice activated by enterprises and, in the other side, the discursive practice imposed by consumers looking for attention for their demands. This tension is determinated by the modes of enunciation and the meaning effects that medium makes possible.